A new transcriptome resource for Cellaria immersa (Phylum: Bryozoa) reveals candidate genes and proteins related to biomineralization - Achilleos, Katerina; Smith, Abigail M.; Kenny, Nathan J.; Brown, Chris M. (Frontiers in Marine Science, 2024)
One of the most salient features of marine bryozoans is their well-calcified skeleton, and many species in this phylum are important reef-builders. To date, the molecular machinery responsible for skeletal formation in these key animals remains unknown. In this study we performed de novo transcriptome assembly from RNA from Cellaria immersa colonies collected in New Zealand, the first from the family Cellariidae. The assembly resulted in a set of 125,750 transcripts and was estimated to be 97.2% complete when compared to BUSCO core gene sets. A function was predicted for 61,442 (48.8%) of the translated proteins, using similarity searches against a range of databases using BLAST and InterProScan. Cellaria species form erect, heavily calcified arborescent colonies, which when abundant can create micro-forests or meadows on the ocean floor. RNA was extracted separately from younger distal and older proximal parts of the colonies, aiming to identify the key genes involved in biomineralization as the young zooids (at the distal growth margin) of the colony are more likely to be actively growing and calcifying compared to the old zooids of the proximal parts of the colony. Differential expression analysis was carried out to identify differential expression between the distal and proximal parts of the colonies. This showed that 506 (2.2%) of the transcripts were expressed more highly in the young zooids and 4,676 (20.4%) were expressed more highly in the old zooids. Over 50 protein families were identified as candidates involved in biomineralization in C. immersa based on the functional annotation, their expression pattern and literature. Transcripts encoding 24 such protein families were more highly expressed in the young zooids. This is the first such study on a heavily calcified species from the phylum Bryozoa, increasing the amount of ‘omics’ data available for C. immersa and the phylum. These data provide a resource for current and future studies of heavily calcified bryozoans, shedding a light on the biomineralization process in this phylum.